Christian Education Curriculum: Discipleship-Based Recovery as a Model for Character Development of Addicts in Drug Rehabilitation Centers - Marsaulina, Roce; Majesty, Gilbert Timothy (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This study investigates the effectiveness of a Christian discipleship-based curriculum for character development in drug rehabilitation, addressing the limitations of conventional approaches that often neglect spiritual dimensions. Using document analysis of rehabilitation curricula and program materials, the research examines how faith-based principles facilitate holistic recovery. The analysis reveals four key findings: First, theological foundations of repentance and redemption provide a unique framework for identity transformation. Second, the curriculum effectively combines biblical teaching with experiential learning methods. Third, the integration of psychological principles with spiritual disciplines creates a synergistic approach to recovery. Fourth, while showing promising results in long-term sobriety and moral development, implementation faces challenges like cultural adaptation and resource constraints. The study demonstrates that discipleship-oriented programs offer distinct advantages by addressing both behavioral and existential aspects of addiction. The curriculum's strength lies in its ability to foster purpose-driven transformation through structured spiritual formation.